Prevención y diagnóstico veterinario de la tuberculosis bovina. Una revisión de las tendencias globales - Domínguez-Odio, Aníbal; González-Marrero, Isbel; Toirac-Proenza, Raiselys; Rodríguez-Coipel, Yudit (Spei Domus, 2019)
Introduction: The bovine tuberculosis (TBb) caused by Mycobacterium Bovis is a serious bacterial, chronic, re-emerging and zoonotic disease. It affects to the livestock production and to the wild and affective animals, also. In the bovine group, it provokes substantial economic losses related with the health measures for its control, and important trade restrictions to the by-products. Because the strategies of prevention and control should be updated regarding to the scientific developments; the study to present the advances and the scientist technological tendencies about the sanitary strategies for the control of the TBb was performed. Methodology: A huge consultation of original articles and a revision on vaccines and diagnosis of TBb between the years 2002 and 2017 in the database of MEDLINE/PubMed, EBSCO and SciELO was carried out. Results: An active and coherent international action orientated to explore vaccinal formulations and advances in diagnostic tools was found. Important advances in the development of immunogens for the cattle were not reported. Both a proof with high values of sensibility (Se) and specificity (Sp) for the populational diagnostic of the disease. Conclusions: It is deemed that the scientific and technological advances obtained over the past years, are not necessarily going to contribute, for the moment, to the success of the national programs of control and eradication of the TBb. Therefore, in this context the prioritization of an integral analysis that considers the realities of every region or country, within the concept: “A single health”, the combined and strategic use of the diagnostic systems, the firm political commitment of the governments and the international cooperation are indispensable to advance in the fight against this disease.